Software analysis, testing, and evolution : 8th International Conference, SATE 2018, Shenzhen, Guangdong, China, November 23-24, 2018, Proceedings /: 8th International Conference, SATE 2018, Shenzhen, Guangdong, China, November 23-24, 2018, Proceedings. (2018) - Unknown
No abstract available